A mullite whisker synthesized at low temperature using desert yellow sand as raw material and a preparation method thereof

By using desert yellow sand, aluminum sulfate and anhydrous sodium sulfate for molten salt synthesis at a temperature of 900 to 1000°C, the problems of high synthesis temperature and high cost of mullite whiskers in the existing technology have been solved, and high efficiency and low cost have been achieved. The cost-effective preparation of mullite whiskers has good aspect ratio and environmental protection performance.

CN114808104BActive Publication Date: 2025-01-24JIANGXI VOCATIONAL & TECH COLLEGE OF CERAMIC ARTS & CRAFTS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210510333.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-11
Publication Date
2025-01-24
Estimated Expiration
2042-05-11

AI Technical Summary

Technical Problem

When synthesising mullite whiskers in the prior art, the reaction temperature is high, the raw material cost is high, and the aspect ratio and purity are difficult to meet the high requirements.

Method used

The desert yellow sand is used as a silicon source, aluminum sulfate is used as an aluminum source, and sodium -free sodium sulfate is used as a melting salt medium. At 900 to 1000 ° C temperature, the low temperature synthesis of Mo Lai stone crystal must be synthetic to reduce the synthetic temperature to avoid high -cost use of high costs. Aluminum fluoride and toxic five oxidation.

Benefits of technology

Under the premise of ensuring high -length diameter than needle -shaped Mo Lai stone crystal beard, effectively reduce the synthetic temperature, reduce production costs, and increase resource utilization, have the advantages of environmental protection and economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114808104B_ABST
    Figure CN114808104B_ABST
Patent Text Reader

Abstract

The invention discloses a mullite whisker synthesized at low temperature using desert yellow sand as raw material and a preparation method thereof, wherein a silicon source is introduced into desert yellow sand, an aluminum source is introduced into aluminum sulfate, corresponding raw materials are weighed based on the mullite theoretical chemical formula ratio and different ratios of rich aluminum and rich silicon, anhydrous sodium sulfate is used as a molten salt medium, mixed and placed in a planetary ball mill for ball milling for 30 minutes, and then the mixture is placed in a crucible and calcined at 800-1100°C for 1-5 h, cooled to room temperature with the furnace, and the molten salt is removed with water, and mullite whiskers can be obtained after filtration and drying. The invention has the advantages that the energy consumption of synthesizing mullite whiskers from desert yellow sand is greatly reduced, and the solid phase method for synthesizing mullite whiskers is reduced by about 300°C, and no expensive whisker promoter aluminum fluoride and toxic substance sintering aid vanadium pentoxide are required, the preparation process is simple, and the cost is low, which effectively promotes the resource utilization of desert yellow sand in the low-temperature synthesis of mullite whiskers, and has greater economic and social value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic non-metallic materials, in particular to a mullite whisker synthesized at low temperature using desert yellow sand as a raw material and a preparation method thereof. Background Art

[0002] As the only stable compound in the aluminosilicate system, mullite is found in low amounts in nature. Natural mullite crystals are slender needle-shaped and have excellent properties, such as good acid and alkali resistance and relatively low thermal expansion coefficient, low specific heat capacity and thermal conductivity, low bulk density, and good thermal shock resistance. Therefore, it is widely used. As a type of fiber material, it is used in ceramic-based composite materials to toughen and strengthen the ceramic matrix. With the continuous development of science and technology, some new processes and technologies are constantly updated, and the demand for mullite whiskers with high aspect ratio, high purity and good dispersibility is also increasing. At present, the main methods for synthesizing mullite whiskers are: mineral high-temperature decomposition method, sol-gel method, precipitation method, hydrothermal method, spray pyrolysis method, electric melting method, solid phase reaction synthesis method, etc. Mullite obtained by high-temperature mineral decomposition often has low purity and too high reaction temperature; while the sol-gel method, spray pyrolysis method, precipitation method, and hydrothermal method have low synthesis temperatures, but they all use high-purity raw materials, so the cost is high; mullite obtained by electric melting method or solid phase reaction synthesis method often has high reaction temperature, and whisker promoters and sintering aids need to be added during the synthesis process, further increasing the cost. Based on the above analysis, it is urgent to find a method with a wide source of raw materials, low price, and low synthesis temperature to synthesize whisker-like mullite crystals.

[0003] The molten salt method is a method that can synthesize mullite crystals at low temperatures. So far, there are few reports on the synthesis of mullite crystals using this method. For example, Zhang Bing et al. used high-purity alumina and silicon oxide as raw materials and potassium sulfate as molten salt medium to synthesize mullite crystals at 1100℃~1300℃. Due to the high synthesis temperature and process requirements, the energy consumption is increased and it is not conducive to actual production; Nie Jianhua, Zhu Boquan et al. used chemical raw materials to prepare mullite whiskers, and the ingredients were prepared according to the Al2O3 / SiO2 molar ratio of 3:2. Although the synthesis temperature was low, there was a prominent disadvantage of high raw material cost, and the effect of the ratio of silicon-rich to aluminum-rich on the synthesis of mullite was not explored; Liu Yin et al. used waste coal gangue as the silicon source, and used the molten salt method with potassium aluminum sulfate as both the molten salt and the aluminum source to synthesize mullite crystals at 850℃~900℃, but the obtained mullite crystals were severely agglomerated and had a relatively low aspect ratio. Summary of the invention

[0004] The purpose of the present invention is to provide a method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand, a low-grade raw material with a wide range of sources, and a preparation method thereof. The present invention can effectively reduce the temperature of synthesizing mullite while ensuring that needle-shaped mullite whiskers with a high aspect ratio are obtained, which is about 300°C lower than the traditional solid phase synthesis temperature, and does not require the addition of expensive aluminum fluoride and toxic vanadium pentoxide, thereby greatly reducing the production cost.

[0005] In order to achieve the above first purpose, the technical solution adopted by the present invention is:

[0006] A method for synthesizing mullite whiskers at low temperature using desert yellow sand as a raw material comprises the following steps: using desert yellow sand as a silicon source, aluminum sulfate as an aluminum source, and anhydrous sodium sulfate as a molten salt medium, calcining and synthesizing mullite whiskers at a temperature of 900-1000°C; after the silicon source and the aluminum source are mixed, the Al2O3 / SiO2 molar ratio is 1.5-2.2; the heating rate during the calcining process is 2-10°C / min, and the insulation time of the highest temperature during the calcining process is 1-5 hours.

[0007] Preferably, after the silicon source and the aluminum source are mixed, the molar ratio of Al2O3 / SiO2 is 3:2, 9:5 or 11:5.

[0008] Preferably, the amount of anhydrous sodium sulfate is determined based on the eutectic temperature of aluminum sulfate and anhydrous sodium sulfate.

[0009] Preferably, the heating rate during the calcination process is 5°C / min.

[0010] Preferably, the holding time at the highest temperature during the calcination process is 3 hours.

[0011] Preferably, the method comprises the following steps: taking desert yellow sand, aluminum sulfate and anhydrous sodium sulfate and uniformly mixing them, placing them in a crucible for calcining, cooling them to room temperature with the furnace, dissolving the molten salt with water, filtering and drying to obtain mullite whiskers.

[0012] Preferably, the steps of dissolving and filtering are: placing the calcined product in a beaker filled with hot water to soak and dissolve, and stirring continuously with a glass rod, and pouring out the supernatant after standing; continuing to add hot water, repeating the above operation several times until no precipitation occurs when a soluble barium salt is added to the supernatant, and mullite whiskers can be obtained after filtering and drying.

[0013] Preferably, the desert yellow sand is obtained by grinding and then passing through a 250-mesh sieve, and the aluminum sulfate and anhydrous sodium sulfate are obtained by passing through a 200-mesh sieve respectively.

[0014] Preferably, the desert yellow sand is ground by dry ball milling with a planetary ball mill for 60 min at a rotation speed of 450 revolutions per minute, and the raw materials are mixed by dry ball milling with a planetary ball mill for 30 min at a rotation speed of 400 revolutions per minute.

[0015] Preferably, the prepared mullite whisker phase is mullite; or mullite is the main crystal phase, corundum or quartz is the secondary crystal phase, and the aspect ratio of the mullite whisker is higher than 32.

[0016] In order to achieve the above second purpose, the technical solution adopted by the present invention is:

[0017] The invention discloses a mullite whisker synthesized at low temperature with desert yellow sand as raw material. The mullite whisker is synthesized by calcining at a temperature of 900-1000°C using desert yellow sand as a silicon source, aluminum sulfate as an aluminum source, and anhydrous sodium sulfate as a molten salt medium. The silicon source and the aluminum source are mixed to obtain an Al2O3 / SiO2 molar ratio of 1.5-2.2. The heating rate during the calcining process is 2-10°C / min, and the maximum temperature holding time during the calcining process is 1-5 hours.

[0018] Preferably, after the silicon source and the aluminum source are mixed, the molar ratio of Al2O3 / SiO2 is 3:2, 9:5 or 11:5.

[0019] Preferably, the amount of anhydrous sodium sulfate is determined based on the eutectic temperature of aluminum sulfate and anhydrous sodium sulfate.

[0020] Preferably, the heating rate during the calcination process is 5°C / min.

[0021] Preferably, the holding time at the highest temperature during the calcination process is 3 hours.

[0022] Preferably, the desert yellow sand is obtained by grinding and then passing through a 250-mesh sieve, and the aluminum sulfate and anhydrous sodium sulfate are obtained by passing through a 200-mesh sieve respectively.

[0023] Preferably, the method comprises the following steps: taking desert yellow sand, aluminum sulfate and anhydrous sodium sulfate and uniformly mixing them, placing them in a crucible for calcining, cooling them to room temperature with the furnace, dissolving the molten salt with water, filtering and drying to obtain mullite whiskers.

[0024] Preferably, the steps of dissolving and filtering are: placing the calcined product in a beaker filled with hot water to soak and dissolve, and stirring continuously with a glass rod, and pouring out the supernatant after standing; continuing to add hot water, repeating the above operation several times until no precipitation occurs when a soluble barium salt is added to the supernatant, and mullite whiskers can be obtained after filtering and drying.

[0025] Preferably, the desert yellow sand is ground by dry ball milling with a planetary ball mill for 60 min at a rotation speed of 450 revolutions per minute, and the raw materials are mixed by dry ball milling with a planetary ball mill for 30 min at a rotation speed of 400 revolutions per minute.

[0026] The beneficial effects of the present invention are:

[0027] The present invention adopts low-grade raw material desert yellow sand, which occupies one-third of the land area, as a silicon source, aluminum sulfate or aluminum hydroxide or potassium aluminum sulfate as an aluminum source, and anhydrous sodium sulfate as a molten salt medium. The temperature of synthesizing mullite can be effectively reduced under the premise of ensuring that needle-shaped mullite whiskers with a high aspect ratio are obtained. The temperature of synthesizing mullite using desert yellow sand as a raw material in a more traditional solid phase method is lower than about 300°C, and there is no need to add expensive aluminum fluoride and toxic vanadium pentoxide as additives, which greatly reduces the production cost. The method can not only efficiently recycle low-grade raw material desert yellow sand, but also widely apply the synthesized mullite whiskers, which plays a certain positive role in environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] FIG. 1 is the XRD diffraction patterns of samples of Examples 1-4 of the present invention.

[0029] FIG2 is the XRD diffraction patterns of samples of Examples 6, 8, 10 and 12 of the present invention, wherein from top to bottom in the figure are the patterns of Examples 6, 8, 10 and 12.

[0030] Attached Figure 3 It is the XRD diffraction pattern of the samples of comparative examples 1-4 of the present invention.

[0031] Attached Figure 4 It is the XRD diffraction pattern of the samples of comparative examples 5-6 of the present invention.

[0032] FIG5 is a SEM photo of the sample of Example 3 of the present invention.

[0033] FIG. 6 is a SEM photograph of the sample of Example 10 of the present invention. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0035] The desert yellow sand used in the embodiment was ground and passed through a 250-mesh sieve, and the aluminum sulfate and anhydrous sodium sulfate were respectively passed through a 200-mesh sieve. The desert yellow sand was ground by dry ball milling with a planetary ball mill for 60 min at a speed of 450 rpm, and the raw materials were mixed by dry ball milling with a planetary ball mill for 30 min at a speed of 400 rpm.

[0036] Example 1 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0037] Weigh desert yellow sand and aluminum sulfate according to the Al2O3 / SiO2 molar ratio of 3:2, weigh the amount of anhydrous sodium sulfate according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate, mix and ball mill, place the mixture in an electric furnace and heat it to 800℃ at 5℃ / min for 3 hours, and cool it to room temperature with the furnace; place the calcined product in a beaker filled with hot water to soak and dissolve, and stir it continuously with a glass rod, pour out the supernatant after standing for 20 minutes; continue to add hot water, repeat the above operation several times, until no precipitation appears when soluble barium salt is added to the supernatant, and obtain a powder after filtration and drying. XRD diffraction detection shows only a small amount of very weak mullite diffraction peak.

[0038] Example 2 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0039] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 3:2, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 900°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. A large number of mullite diffraction peaks were found in the XRD diffraction test.

[0040] Example 3 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0041] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 3:2, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 1000°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. A large number of mullite diffraction peaks were found in the XRD diffraction test. Figure 5 This is a SEM photo of the prepared sample. The more obvious mullite whiskers in the picture are selected. According to the measurement based on the ruler, the diameter of the mullite whiskers is 0.1-0.12 μm, the length of the mullite whiskers is 3.2-4.1 μm, and the aspect ratio is higher than 32.

[0042] Example 4 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0043] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 3:2, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 1100 ℃ at 5 ℃ / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 min, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant. The powder was obtained after filtration and drying. XRD diffraction detection found that the diffraction peak intensity of mullite was weakened compared with the synthetic peak at 1000 ℃, and other impurities were produced, indicating that part of the mullite crystals were decomposed at this temperature.

[0044] Example 5 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0045] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 6:5, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 900°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. XRD diffraction detection found diffraction peaks of mullite and quartz.

[0046] Example 6 Method for synthesizing mullite whiskers at low temperature using desert yellow sand as raw material by molten salt method

[0047] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 6:5, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 1000°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. XRD diffraction detection found diffraction peaks of mullite and quartz.

[0048] Example 7 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0049] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 9:5, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 900°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. A large number of mullite diffraction peaks were found in the XRD diffraction test.

[0050] Example 8 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0051] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 9:5, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 1000°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. A large number of mullite diffraction peaks were found in the XRD diffraction detection.

[0052] Example 9 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0053] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 11:5, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 900°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. A large number of mullite diffraction peaks were found in the XRD diffraction detection.

[0054] Example 10 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0055] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 11:5, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 1000°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. A large number of mullite diffraction peaks were found in the XRD diffraction test. Figure 6 This is the SEM photo of the prepared sample. The more obvious mullite whiskers in the picture are selected. According to the measurement based on the ruler, the diameter of the mullite whiskers is 0.17-0.2 μm, the length of the mullite whisker diameter is 4.36-5.48 μm, and the aspect ratio is higher than 26.

[0056] Example 11 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0057] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 29:10, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 900°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. XRD diffraction detection found diffraction peaks of mullite and corundum.

[0058] Example 12 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0059] Desert yellow sand and aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 29:10, and the amount of anhydrous sodium sulfate was weighed according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 1000°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. XRD diffraction detection found diffraction peaks of mullite and corundum.

[0060] Example 13 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0061] Weigh desert yellow sand and aluminum sulfate according to the Al2O3 / SiO2 molar ratio of 11:5, weigh the amount of anhydrous sodium sulfate according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate, mix and ball mill, place the mixture in an electric furnace and heat it to 1000°C at 5°C / min for 1 hour, and cool it to room temperature with the furnace; place the calcined product in a beaker filled with hot water to soak and dissolve, and stir it continuously with a glass rod, pour out the supernatant after standing for 20 minutes; continue to add hot water, repeat the above operation several times, until no precipitate appears when a soluble barium salt is added to the supernatant, and after filtering and drying, only a small amount of very weak mullite diffraction peak is detected by XRD diffraction.

[0062] Example 14 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0063] Weigh desert yellow sand and aluminum sulfate according to the Al2O3 / SiO2 molar ratio of 11:5, weigh the amount of anhydrous sodium sulfate according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate, mix and ball mill, place the mixture in an electric furnace and heat it to 1000°C at 5°C / min for 5 hours, and cool it to room temperature with the furnace; place the calcined product in a beaker filled with hot water to soak and dissolve, and stir it continuously with a glass rod, pour out the supernatant after standing for 20 minutes; continue to add hot water, repeat the above operation several times, until no precipitate appears when a soluble barium salt is added to the supernatant, and after filtering and drying, only a small amount of very weak mullite diffraction peak is detected by XRD diffraction.

[0064] Example 15 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0065] Weigh desert yellow sand and aluminum sulfate according to the Al2O3 / SiO2 molar ratio of 11:5, weigh the amount of anhydrous sodium sulfate according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate, mix and ball mill, place the mixture in an electric furnace and heat it to 1000°C at 2°C / min for 3 hours, and cool it to room temperature with the furnace; place the calcined product in a beaker filled with hot water to soak and dissolve, and stir it continuously with a glass rod, pour out the supernatant after standing for 20 minutes; continue to add hot water, repeat the above operation several times, until no precipitate appears when a soluble barium salt is added to the supernatant, and after filtering and drying, only a small amount of very weak mullite diffraction peak is detected by XRD diffraction.

[0066] Example 16 Method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material

[0067] Weigh desert yellow sand and aluminum sulfate according to the Al2O3 / SiO2 molar ratio of 11:5, weigh the amount of anhydrous sodium sulfate according to the low eutectic temperature of aluminum sulfate and anhydrous sodium sulfate, mix and ball mill, place the mixture in an electric furnace and heat it to 1000°C at 10°C / min for 3 hours, and cool it to room temperature with the furnace; place the calcined product in a beaker filled with hot water to soak and dissolve, and stir it continuously with a glass rod, pour out the supernatant after standing for 20 minutes; continue to add hot water, repeat the above operation several times, until no precipitate appears when a soluble barium salt is added to the supernatant, and after filtering and drying, only a small amount of very weak mullite diffraction peak is detected by XRD diffraction.

[0068] Comparative Example 1

[0069] Desert yellow sand and potassium aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 3:2. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 800°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant. After filtration and drying, a powder was obtained, and only a small amount of very weak mullite diffraction peaks were detected by XRD diffraction.

[0070] Comparative Example 2

[0071] Desert yellow sand and potassium aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 3:2. After mixing and ball-milling, the mixture was placed in an electric furnace and heated to 900°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant. After filtration and drying, a powder was obtained, and only a small amount of very weak mullite diffraction peaks were detected by XRD diffraction.

[0072] Comparative Example 3

[0073] Desert yellow sand and potassium aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 11:5. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 800°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant. After filtration and drying, a powder was obtained, and only a small amount of very weak mullite diffraction peaks were detected by XRD diffraction.

[0074] Comparative Example 4

[0075] Desert yellow sand and potassium aluminum sulfate were weighed according to the Al2O3 / SiO2 molar ratio of 11:5. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 900°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant. After filtration and drying, a powder was obtained, and only a small amount of very weak mullite diffraction peaks were detected by XRD diffraction.

[0076] Comparative Example 5

[0077] Desert yellow sand and aluminum hydroxide were weighed according to the Al2O3 / SiO2 molar ratio of 3:2, and molten salt was weighed according to the mass ratio of aluminum hydroxide and anhydrous sodium sulfate of 1:1. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 900°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. No mullite diffraction peak was found in the XRD diffraction test.

[0078] Comparative Example 6

[0079] Desert yellow sand and aluminum hydroxide were weighed according to the Al2O3 / SiO2 molar ratio of 3:2, and molten salt was weighed according to the mass ratio of aluminum hydroxide and anhydrous sodium sulfate of 1:1. After mixing and ball milling, the mixture was placed in an electric furnace and heated to 950°C at 5°C / min for 3 hours, and then cooled to room temperature with the furnace; the calcined product was placed in a beaker filled with hot water to soak and dissolve, and stirred continuously with a glass rod. After standing for 20 minutes, the supernatant was poured out; hot water was continued to be added, and the above operation was repeated several times until no precipitation appeared when a soluble barium salt was added to the supernatant, and a powder was obtained after filtration and drying. No mullite diffraction peak was found in the XRD diffraction test.

[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A method for synthesizing mullite whiskers at low temperature using desert yellow sand as raw material, characterized in that: The method comprises the following steps: using desert yellow sand as a silicon source, aluminum sulfate as an aluminum source, and anhydrous sodium sulfate as a molten salt medium, and calcining at a temperature of 900-1000 DEG C to synthesize mullite whiskers; the silicon source and the aluminum source are mixed, and the molar ratio of Al2O3 to SiO2 is converted to 1.5-2.2; the heating rate during the calcining process is 5 DEG C / min, and the insulation time of the highest temperature during the calcining process is 1-5 hours; and the amount of anhydrous sodium sulfate is determined according to the low eutectic point temperature of aluminum sulfate and anhydrous sodium sulfate.

2. The method for synthesizing mullite whiskers at low temperature using desert yellow sand as raw material according to claim 1, characterized in that: After the silicon source and the aluminum source are mixed, the molar ratio of Al2O3 / SiO2 is 3:2, 9:5 or 11:

5.

3. The method for synthesizing mullite whiskers at low temperature using desert yellow sand as raw material according to claim 1, characterized in that: The holding time at the highest temperature during the calcination process was 3 hours.

4. The method for synthesizing mullite whiskers at low temperature using desert yellow sand as raw material according to claim 1, characterized in that: The method comprises the following steps: taking desert yellow sand, aluminum sulfate and anhydrous sodium sulfate and uniformly mixing them, placing them in a crucible for calcining, cooling them to room temperature with the furnace, dissolving the molten salt with water, filtering and drying to obtain mullite whiskers.

5. The method for synthesizing mullite whiskers at low temperature using desert yellow sand as raw material according to claim 4, characterized in that: The steps of dissolving and filtering are as follows: placing the calcined product in a beaker filled with hot water to soak and dissolve, and stirring continuously with a glass rod, and pouring out the upper clear liquid after standing; continue to add hot water, repeat the above operation several times until no precipitation occurs when a soluble barium salt is added to the upper clear liquid, and mullite whiskers can be obtained after filtering and drying.

6. The method for synthesizing mullite whiskers at low temperature using desert yellow sand as raw material according to any one of claims 1 to 5, characterized in that: The desert yellow sand is obtained by grinding and passing through a 250-mesh sieve, and the aluminum sulfate and anhydrous sodium sulfate are obtained by passing through a 200-mesh sieve respectively.

7. The method for synthesizing mullite whiskers at low temperature by molten salt method using desert yellow sand as raw material according to claim 6, characterized in that: The desert yellow sand is ground by dry ball milling with a planetary ball mill for 60 minutes at a rotation speed of 450 revolutions per minute, and the raw materials are mixed by dry ball milling with a planetary ball mill for 30 minutes at a rotation speed of 400 revolutions per minute.

Citation Information

Patent Citations

  • Mullite nano-whisker prepared by using pyrite tailing as raw material and preparation method of mullite nano-whisker

    CN104313695A

  • Process for preparing mullite crystal whisker by molten salt method

    CN1884192A